Anti-HFRS Human IgG Produced in Transchromosomic Bovines Has Potent Hantavirus Neutralizing Activity and Is Protective in Animal Models - Perley, Casey C.; Brocato, Rebecca L.; Wu, Hua; Bausch, Christoph; Karmali, Priya P.; Vega, Jerel B.; Cohen, Melanie V.; Somerville, Brandon; Kwilas, Steven A.; Principe, Lucia M.; Shamblin, Joshua; Chivukula, Padmanabh; et al. (Frontiers in Microbiology, 2020)
We explored an emerging technology to produce anti-Hantaan virus (HTNV) and anti-Puumala virus (PUUV) neutralizing antibodies for use as pre- or post-exposure prophylactics. The technology involves hyperimmunization of transchomosomic bovines (TcB) engineered to express human polyclonal IgG antibodies with HTNV and PUUV DNA vaccines encoding GnGc glycoproteins. For the anti-HTNV product, TcB was hyperimmunized with HTNV DNA plus adjuvant or HTNV DNA formulated using lipid nanoparticles (LNP). The LNP-formulated vaccine yielded 5-fold higher neutralizing antibody titers using 10-fold less DNA. Human IgG purified from the LNP-formulated animal (SAB-159), had anti-HTNV neutralizing antibody titers >100,000. SAB-159 was capable of neutralizing pseudovirions with monoclonal antibody escape mutations in Gn and Gc demonstrating neutralization escape resistance. SAB-159 protected hamsters from HTNV infection when administered pre- or post-exposure, and limited HTNV infection in a marmoset model. An LNP-formulated PUUV DNA vaccine generated purified anti-PUUV IgG, SAB-159P, with a neutralizing antibody titer >600,000. As little as 0.33 mg/kg of SAB-159P protected hamsters against PUUV infection for pre-exposure and 10 mg/kg SAB-159P protected PUUV-infected hamsters post-exposure. These data demonstrates that DNA vaccines combined with the TcB-based manufacturing platform can be used to rapidly produce potent, human, polyclonal, escape-resistant anti-HTNV and anti-PUUV neutralizing antibodies that are protective in animal models.